TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT IN THE DIGITAL ERA (CASE STUDY OF TUGALA LAURU VILLAGE OFFICES) - Septeradenus Zebua; Meiman Hidayat Waruwu; Robin Markus Putra Waruwu; Palindungan Lahagu (LPPM YPITI, 2026)
This study aims to determine the process of Human Resource Management (HRM) transformation in the digital era in Tugala Lauru Village, identify the challenges faced, and formulate strategies used. The background of the study is based on the demand for digitalization of village administration through the implementation of the Village Financial System (SISKEUDES) which changes work patterns and organizational culture. The research method uses a qualitative case study approach with six key informants, including the village head, village secretary, and village officials. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using thematic analysis techniques. The results of the study indicate the digitalization of village administration and finance, increased competency of officials through basic training, and changes in work culture to be more rapid, structured, and transparent. Challenges faced include limited digital competence, suboptimal technological infrastructure, and resistance to change. The strategies implemented include support from village leadership, procurement of technological facilities through the Village Budget (APBDes), and participation of officials in training organized by the local government.